Low-liver-accumulation lipid nanoparticles enhance the efficacy and safety of HPV therapeutic tumor vaccines - Xiaodie Wang; Zhidan Tian; Meng Wang; Xiaoru Cai; Shuyan Yang; Jianyao Zeng; Yuan Fang; Xuesen Bai; Pei Wang; Yan Sun; Chuanxin Guo; Tao Liu; et al. (Journal of Translational Medicine)
Abstract Background Lipid nanoparticles (LNPs) hold significant potential in vaccine and cancer therapy, but conventional LNPs often cause hepatotoxicity and reduced efficacy due to liver accumulation. Methods LNP molecules with varying tail lengths were synthesized in vitro. Transfection efficiency was assessed in vitro via flow cytometry. The BALB/c model was used to evaluate in vivo delivery efficiency of the LNPs. The C57BL/6 mouse model was used to evaluate in vivo anti-tumor pharmacodynamics, along with tumor-infiltrating immune cells and serum inflammatory cytokines. The Sprague Dawley (SD) rat model was used for toxicity testing of the candidate LNP. Results Lipid 7 demonstrated threefold higher mRNA expression efficiency at the injection site while minimizing liver retention. In an HPV tumor model, Lipid 7 achieved tumor suppression comparable to SM-102-based LNP but outperformed in remodeling the tumor microenvironment (dendritic cells: 12.1% vs. 5.1%; natural killer cells: 1.1% vs. 0.5%) and elevating serum immune cytokines (TNF-α, IL-1β, etc., 1.2–1.8-fold higher). Critically, Lipid 7 reduced off-target mRNA accumulation in the heart, liver, spleen, lungs, and kidneys, mitigating hepatotoxicity risks associated with traditional LNPs. Conclusions By employing a novel, non-patented ionizable lipid design, this work balances delivery efficiency and biosafety, Lipid 7 offers a high-efficacy, low-toxicity therapeutic strategy for HPV-related cancers. Graphical Abstract